The effect of expense ratio, fund size and fund age on performance of ETF mutual funds with interest rate as a moderating variable - Audita, Atika Yasyfa; Iskandar, Rusdiah; Azis, Musdalifah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The focus of this study is to exploraton the impact of expense ratio, fund size, and fund age on ETF mutual fund performance with interest rates as a moderating. The population is ETF Mutual Funds registered with the Financial Services Authority (OJK) using a purposive sampling technique in taking a sample of 20 Mutual Funds with an observation period of 4 years. The review technique used in this  evidence is the moderated regression analysis (MRA) with the STATA 17 program to tabulate the data. These findings indicate that the expense ratio has a positive and insignificant effect on the sharpe ratio; fund size has a negative and significant effect on the sharpe ratio; fund age has a positive and significant effect on the sharpe ratio; then, the interest rate is not a moderating variable that influences the expense ratio positively and is not significant to the sharpe ratio; interest rate is not a moderating variable that affects fund size negatively and significantly to the sharpe ratio; while the interest rate is a moderating variable that influences fund age positively and significantly to the sharpe ratio.